Group Conseling with Self-Instruction Techniques and Cognitive Restructuring Techniques to Reduce Academic Anxiety - Mafirja, Sulma; Wibowo, Mungin Eddy; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2018)
The purpose of this research was to examine the effectiveness of counseling in the group of self-instruction techniques and cognitive restructuring techniques to reduce students' academic anxiety. This research uses 2 x 2 Factorial Design, applied to students as many as 31 students in Public Senior High School 12 Semarang. The instrument used was the Academic Achievement Questionnaire with a sub-scale of learning-related anxiety, class-related anxiety and test anxiety. Data analysis techniques used are 2-way ANAVA test and the mean difference. The results showed that counseling in the group of self-instruction techniques and cognitive restructuring techniques were effective to reduce students' academic anxiety. The findings of this research prove the effectiveness of group counseling services with self-instruction techniques and cognitive restructuring techniques for students in the city of Semarang Indonesia.